Influence of career anchors, work values, personality traits towards employability orientation among Malaysian university students - D’ Silva, Jeffrey Lawrence; Abdul Hamid, Jamaliah (Canadian Center of Science and Education, 2014)
Work environment is facing numerous challenges and this entails organizations to better understand the phenomenon of employability orientation. Thus, the primary aim of this study is to determine the level of employability orientation among university students and its influencing factors. This is a quantitative study whereby a total of 711 undergraduates were randomly selected from public universities in Malaysia to participate in the study. The dependent variable of this study was employability orientation and the independent variables were career anchors, work values and personality traits. The principal result of this study showed that there were eight sub-dimensions that contributed around 52.0% of the variation in employability orientation. It is believed that the findings will provide some interesting input in understanding the complexities associated with employability orientation among university students.